A recurrent variant in PPP2R5C identified in individuals with macrocephaly, intellectual disability, and seizures - Alison M. Muir; Adi Reich; Fanggeng Zou; Deanna Alexis Carere; Sue Moyer Harasink; Lily Tran; Bobbi McGivern (HGG Advances)
Summary: PPP2R5C encodes a B-type regulatory subunit of protein phosphatase 2A (PP2A). This protein serine/threonine phosphatase is a component of multiple signaling pathways and is an established negative regulator of cell division, growth, and proliferation. De novo variants in other subunits of PP2A are associated with neurodevelopment disorders and intellectual disability (ID). We report two unrelated affected individuals with a recurrent variant in PPP2R5C (c.457G>A: p.(Glu153Lys)). Core features in affected individuals include macrocephaly, ID, hypotonia, and seizures. The Glu153 residue is part of a highly conserved acidic loop and directly interacts with the PP2A catalytic subunit. Our results support heterozygous PPP2R5C missense variants as a potential cause of macrocephaly and neurodevelopmental disorder.